Verdant Power : a case of ethical leadership - Mulloth, Bala; Griffiths, Mark D.; Kickul, Jill (London : NeilsonJournals Publishing, 2012)
We describe the ethical leadership dilemmas confronting Verdant Power. Formed in 2000, this New York City marine renewable energy company develops projects and technology that delivers electricity directly into the local power grid. Set in early 2010, the case outlines the tensions, challenges and costs (both financial and time) that management faces as it attempts to commercialize a technology in an industry with strict and rigid regulatory policies. The key teaching objectives of the case include a) understanding the leadership role that the company must assume in paving the way for regulatory reform for US-based marine renewable technology ventures, and b) appreciating the importance and implications of sustainability given the pursuit of the financial and environmental mission of the founders.
Originally Published InMulloth, B., Griffiths, M. D., & Kickul, J. (2012). Verdant Power: A case of ethical leadership. Journal of Business Ethics Education, 9(1), 447-468. JBEE9-0CS4.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Verdant Power -- Case studies; Ocean energy resources -- New York (State) -- New York -- Case studies; Renewable energy sources -- New York (State) -- New York -- Case studies; Energy conservation -- New York (State) -- New York -- Case studies